Faktor-Faktor yang Mempengaruhi Minat Masyarakat dalam Menggunakan Produk Perbankan Syariah dengan Religiusitas Sebagai Variabel Moderasi - Mulyani, Listi; Moh. Huzaini, (EKOMA : Jurnal Ekonomi, Manajemen, Akuntansi, 2024)
This study examines the factors influencing interest in using Islamic banking products, including knowledge about Islamic banking, risk perception, trust in Islamic banks, and religiosity as a moderating variable. The researchers conducted multiple linear regression analysis using a closed questionnaire. The results showed that knowledge about Islamic banking positively influences public interest, implying that a better understanding of Islamic banking products increases interest in using them. However, risk perception does not significantly affect public interest, suggesting that views on risk are not the main factor in choosing these products. Trust in Islamic banks also plays a crucial role in increasing interest, but religiosity does not moderate this relationship. This implies